Martin Seligman and Avicenna on Happiness - Asep Awaludin (Universitas Darussalam Gontor, 2017)
As the ultimate goal of every living soul, happiness has its own place in the hearts of the seekers and in the thoughts of the researchers. Being an elusive term to be discussed for its subjective meaning, happiness utilizes many disciplines of knowledge to be defined and understood fully. The idea of this study was to elaborate on the concept so the researchers might compile it in such a systematic way as to permit anyone to gain knowledge from it and lead them to attain true happiness. For this purpose, there should be prominent figures to obtain from them their ideas on the related concept. They are Martin Seligman and Avicenna; both are, no doubt, exemplary figures and exact credible persons for this study about happiness. This work attempts to analyze and compare their ideas on happiness. Each of them has their own unique concept of happiness since both come from very different backgrounds of study and worldviews. The results show that since Seligman brings his agenda in secular scientific positive psychology, as he stated. While Seligman stops in the temporary world, Avicenna on the other hand, does not. This is because Avicenna based his notion of happiness on a philosophical-religious approach. He emphasized that it is only through the knowledge of true reality i.e. God, one may then achieve absolute and true happiness, although, the conception he conducted was less applicative.